Catalytic activity of C60 fullerene nanowhisker–zeolitic imidazolate framework-67 composite for reduction of 4-nitrophenol. Issue 1 (2nd January 2023) - Ko, Jeong Won; Ko, Weon Bae
Abstract: The liquid–liquid interfacial precipitation method was used to prepare C60 fullerene nanowhisker (FNW)–zeolitic imidazolate framework-67 (ZIF-67) composite from a ZIF-67 solution, C60 -saturated toluene, and isopropyl alcohol. X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) were used to characterize the synthesized C60 FNW-ZIF-67 composite. Its catalytic activity for the reduction of 4-nitrophenol was confirmed by UV–visible (UV-vis) spectroscopy. C60 FNW–ZIF-67 as a catalyst displayed a reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) for 20 min with a rate constant of 1.379 × 10 −1  min −1 (at 25 °C), 5.761 × 10 −2  min −1 (at 15 °C), and 3.113 × 10 −2  min −1 (at 5 °C), respectively. A kinetics study indicated that the hybrid nanocomposite catalyzed the reduction of 4-nitrophenol according to a pseudo-first-order reaction rate equation. The thermodynamic parameters of activation, namely, the enthalpy of activation (Δ H ) of 48.966 kJ mol −1, the entropy of activation (Δ S ) of −97.479 J mol −1 K −1, and the activation energy (Δ E a ) of 51.167 kJ mol −1, were obtained using the Eyring and Arrhenius equations.